The Effect of Tyre and Road Wear Particles on the Terrestrial Isopod Armadillidium pallasii - Giorgia Torreggiani; Chiara Manfrin; Anita Giglio; Andrea Dissegna; Cinzia Chiandetti; Paola Giotta; Monia Renzi; Serena Anselmi; Tecla Bentivoglio; Agnieszka Babczyńska; Silvia Battistella; Paolo Edomi; et al. (Biomolecules)
(1) Car tyre microplastic particles (TMPs) significantly contribute to global microplastic pollution, with an estimated annual production of 6 million tonnes. However, the impact of TMPs, particularly tyre and road wear particles (TRWPs), resulting from tyre abrasion on the road on terrestrial organisms, is poorly understood. This study investigated the effects of TMPs and TRWPs on the growth, immune response, behaviour, and cognition of the woodlouse Armadillidium pallasii over 30 days; (2) TMPs and TRWPs were mixed together in the first experiment and provided at different concentrations of 1.25%, 2.5%, 5%, and 10% (w/w), and with soil at 5% and 10% (w/w) concentrations in the second experiment. (3) No differences in survival or immune responses were observed in both experiments. However, isopods exposed to TRWPs showed significant weight gain at lower concentrations but no gain at higher levels. Behavioural tests revealed increased vigilance in TRWP-exposed animals. Micro-FTIR analysis showed that the number of TMPs and TRWPs in the isopods correlated with soil concentrations, and particle size decreased during the experiment. (4) The study highlights the physiological and behavioural effects of TRWPs and the role of detritivorous species in the biofragmentation of TMPs and TRWPs, contributing to the biogeochemical plastic cycle.